Venous Sinus Stenting Alone as an Effective Treatment for Complex Dural Arteriovenous Fistulas with Sinus Thrombosis - Maximilian Thormann; Roland Schwab; Anastasios Mpotsaris; Maciej Powerski; Daniel Behme (Neurointervention)
Dural arteriovenous fistulas (dAVFs) are rare vascular malformations, often complicated by sinus thrombosis and cortical reflux. We report a patient with a Cognard Type IIb dAVF at the right transverse sinus and ipsilateral sigmoid sinus thrombosis, unsuitable for conventional embolization due to contralateral sinus hypoplasia. A novel therapeutic approach involving direct jugular vein puncture, venous recanalization, and stenting using a stiff 0.035-inch guidewire effectively downgraded the dAVF to Cognard Type I. At 3-month follow-up, stable angiographic outcomes, marked clinical improvement, and absence of seizures confirmed the efficacy of sinus stenting as a standalone treatment in an anatomically challenging case.